Fetal–neonatal exposure to antibiotics and NEC development: A systematic review and meta-analysis - Klerk, Daphne H.; van Avezaath, Lisanne K.; Loeffen, Erik A. H.; Hulscher, Jan B. F.; Kooi, Elisabeth M. W. (Frontiers in Pediatrics, 2023)
Background Fetal and neonatal exposure to antibiotics may contribute to the development of necrotizing enterocolitis (NEC) in preterm infants. This systematic review and meta-analysis investigate whether exposure to third trimester maternal antibiotics (MAB) and/or prolongation of empirical antibiotics (PEAB) are associated with NEC development in preterms. Method We included observational and randomized controlled studies, including those on preterm or very low birth weight (VLBW) infants, from MEDLINE and EMBASE, published between 1990 and June 2021. Exposure was defined as third trimester MAB and/or PEAB. The two reviewers independently performed study selection, data extraction, and quality assessment. Results Three cohort studies compared third trimester MAB with no antibiotics. MAB was associated with lower NEC incidence, unadjusted pooled odds ratio (OR) is 0.57 (95% CI: 0.35–0.93). Twelve cohort studies showed that PEAB was associated with an increased risk of NEC. Ten observational cohort studies show an unadjusted OR of 2.72 (1.65–4.47), and two case–control studies show an unadjusted mean difference of 2.31 (0.94–3.68). Moderate to substantial heterogeneity was observed but decreased in studies with low risk of bias and large sample size. Conclusion Evidence suggests an association between MAB and decreased risk of NEC and an association between PEAB and increased risk of NEC. Further studies should confirm these associations and explore causality. Systematic Review Registration identifier [CRD42022304937].